2013
DOI: 10.1680/geng.12.00037
|View full text |Cite
|
Sign up to set email alerts
|

Thermal response testing through the Chalk aquifer in London, UK

Abstract: Thermal conductivity of the ground is an important parameter in the design of ground energy systems, which have an increasing role to play in providing renewable heat to the built environment. For larger schemes, the bulk thermal conductivity of the ground surrounding the system is often determined in situ using a thermal response test. Although this test method is commonly used, its limitations are often not fully understood, leading to an over-simplistic interpretation that may fail to identify key facets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…It should be noted that these conclusions correspond to a conduction dominated heat transfer case and are not be applicable in the case of dominant groundwater effects, where the TRT interpretation cannot provide a unique value for the effective thermal conductivity (Loveridge et al, 2013). The BHE behaviour could vary for the different applied modes (heat injection, heat extraction, recovery), depending on the characteristics of the aquifer, and TRT data of a long duration could be critical for verifying the modelling of the water flow characteristics.…”
Section: Discussionmentioning
confidence: 92%
“…It should be noted that these conclusions correspond to a conduction dominated heat transfer case and are not be applicable in the case of dominant groundwater effects, where the TRT interpretation cannot provide a unique value for the effective thermal conductivity (Loveridge et al, 2013). The BHE behaviour could vary for the different applied modes (heat injection, heat extraction, recovery), depending on the characteristics of the aquifer, and TRT data of a long duration could be critical for verifying the modelling of the water flow characteristics.…”
Section: Discussionmentioning
confidence: 92%
“…The first method consists in temperature logging along the borehole, usually by lowering a temperature probe into the U-pipe and measuring the temperature at several depth intervals or by installed temperature sensors or fiber optic cables along the [17,18]. The second method consists in circulating the fluid inside the pipe loops without heat injection and recording the temperature at the pipe inlet and outlet.…”
Section: Introductionmentioning
confidence: 99%
“…The second method is widely applied, since it consists in the preliminary phase of a Thermal Response Test (TRT). It has a typical duration of 2 h -12 h [18]. The accuracy of this method depends on the accuracy of the measurement equipment and on the heat added to the circulating fluid due to friction and the pump work.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods rely on temperature measurements taken at multiple depths along the borehole, using downhole sensors placed in the grout, or inside or outside the ground heat exchanger pipes. A distributed thermal response test [107,[141][142][143][144][145] is very similar to a standard thermal response test. It consists in injecting heat to, or extracting heat from, the borehole heat exchanger at constant power and measuring thermal response of the ground at multiple instances along the borehole depth.…”
Section: Distributed and Enhanced Thermal Response Testingmentioning
confidence: 99%
“…Several recent studies have demonstrated the advantages of distributed and enhanced thermal response tests over conventional tests. These tests have been successfully used to identify and characterise hydraulic fractures (e.g., [144,147]) and ground layers (e.g., [141][142][143]). An example is also presented here to demonstrate the advantages of a distributed temperature sensing-based thermal response test over a conventional test.…”
Section: Distributed and Enhanced Thermal Response Testingmentioning
confidence: 99%